Implementation of Cooperative Learning Type Team Games Tournament (TGT) to Improve Students' Understanding of Mathematical Concepts on Fractions at SDN 07 Tilamuta - Winda Anggriyani Uno (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to implement the cooperative learning model of Team Games Tournament (TGT) to improve students' understanding of mathematical concepts on fractions at SDN 07 Tilamuta. The research method used is classroom action research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study were 30 fifth-grade students. The results indicate that the application of the TGT learning model can enhance students' understanding of mathematical concepts. This is evidenced by the increase in the average test scores of concept understanding in each cycle. In the first cycle, the average student score was 65, which increased to 80 in the second cycle. Furthermore, students' learning activities also improved, marked by their active participation in group discussions and game tournaments. In conclusion, the implementation of the TGT cooperative learning model is effective in improving students' understanding of mathematical concepts on fractions at SDN 07 Tilamuta. It is recommended that teachers consider using this learning model in teaching mathematics for other topics as well.